Put Your Money Where Your Mouth Is! Explaining Collective Action Tendencies Through Group-Based Anger and Group Efficacy. (article). - Zomeren, Martijn van
Insights from appraisal theories of emotion are use to integrate elements of theories on collective action. Three experiments with disadvantaged groups systematically manipulated procedural fairness. (Study 1), emotional social support (Study 2) and instrumental social support (Study 3) to examine their effects on collective action tendencies through group-based anger and group efficacy. Results of structural equation modeling showed that procedural fairness and emotional social support affected the group-based anger pathway (reflecting emotion-focused coping), whereas instrumental social support affected the group efficacy pathway (reflecting problem-focused coping). constituting 2 distinct pathways to collective action tendencies. Analyses of the means suggest that collective action tendencies become stronger the more fellow group members :put their money where their mouth is." The authors discuss how their dual pathway model integrates and extends elements of current approaches to collective action. -- (from the author)-- ( from the author).
Keywords: Psychology-Periodicals.